Engaging the online learner, updated : activities and resources for creative instruction - Conrad, Rita-Marie.; Donaldson, J. Ana. (San Francisco : Jossey-Bass, 2011)
"This is a revision of the first title in Jossey-Bass' Online Teaching & Learning series. This series helps higher education professionals improve the practice of online teaching and learning by providing concise, practical resources focused on particular areas or issues they might confront in this new learning environment. This revision includes updated activities and resources for instructors teaching online. Based on changes in technology and best practices learned from the field the revision provides new information for even seasoned online instructors." -- Provided by publisher.
Includes bibliographical references and index.
Keywords: Inclusive education; Computer-assisted instruction; Education -- Effect of technological innovations on